Comparison of maximal heart rate attained by distinct methods - doi: 10.4025/reveducfis.v23i2.12311 - Eduardo Lucia Caputo; Marcelo Cozzensa da Silva; Airton Rombaldi (Journal of Physical Education (Maringá), 2012)
Despite being an indicator that displays simplicity and low cost to be measured, the maximum heart rate has limitations for exercise prescription. The objectives of this study were to compare the HRmax obtained by different methods and verify the agreement between the measurements in adolescents. Participants were 10 adolescent males and 13 females, practitioners of Handball. We considered three measures of heart rate: a direct, obtained at the end of a maximal exercise test by Leger's protocol, and two indirect, predicted by the equations of ACSM (2009) and Tanaka et al.(2001). HRmax measured at the end of maximal exercise test was significantly lower than those predicted by the equations, and reliability analysis showed that the directly measured values ​​do not agree with the values ​​generated by the prediction equations. We can conclude that the predictive equations overestimate HRmax values​​in adolescents.